2018
DOI: 10.3390/polym10040420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polysiloxanes on Roughness and Durability of Basalt Fibres–Reinforced Cement Mortar

Abstract: The influence of roughness and the way it affects the adhesion properties and surface free energy (SFE) of polysiloxanes hydrophobised basalt fibres–reinforced cement mortars were determined in this article. The physical properties of mortars were investigated in the experimental part, which also explored the impact of hydrophobisation and basalt fibres (BF) addition on SFE, frost resistance, contact angle (CA), and roughness. A device capable of calculating all parameters was used to indicate the surface roug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 43 publications
5
29
0
Order By: Relevance
“…The efficiency of silanes compared to standard samples was 77%. The research on the SFE of materials with cement was presented in the numerous papers [57,[79][80][81]. The studies indicated that SFE for building materials surfaces ranges from 50 to 100 mJ•m −2 .…”
Section: A28mentioning
confidence: 99%
“…The efficiency of silanes compared to standard samples was 77%. The research on the SFE of materials with cement was presented in the numerous papers [57,[79][80][81]. The studies indicated that SFE for building materials surfaces ranges from 50 to 100 mJ•m −2 .…”
Section: A28mentioning
confidence: 99%
“…The adhesion of asphalt to the aggregate depends on numerous factors. The basic parameters determining the suitability of an aggregate for a mineral–asphalt mixture are its wettability and roughness [ 39 , 40 ]. If a surface is uneven this improves the mechanical adhesion between the binder and the surfaces of the aggregate grains.…”
Section: Introductionmentioning
confidence: 99%
“…If a surface is uneven this improves the mechanical adhesion between the binder and the surfaces of the aggregate grains. The contact angle (CA) and surface free energy (SFE) are the parameters that describe these phenomena in a detailed way [ 39 , 40 , 41 , 42 , 43 ]. There are several methods for determining these parameters, e.g., the Owens–Wendt, Neumann, Fowkes, Wu, Zisman, and van Oss–Chaudhury–Good methods [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The studies by Praveenkumar et al [5] on cement concrete with the addition of TiO 2 nanomolecules and 10% rice husk enabled the obtaining of a material with greater compressive and flexural strength, as well as enhanced resistance to the effect of chlorides and acids. The addition Quartz sand (0-2 mm) is characterized by specific gravity of 2650 kg/m 3 ; water absorption amounts to 1.2%, while the moisture content equals 0.16% [28]. Table 2 presents the CEM I 32.5R Portland cement parameters.…”
Section: Introductionmentioning
confidence: 99%
“…11, x FOR PEER REVIEW 9 of 2028 days, in relation to the reference samples). The authors believe that it has an effect of the nanomaterial production process.…”
mentioning
confidence: 99%